Emotional Intelligence and Cultural Intelligence and Attitudes towards Team-Based Assessment Courses among undergraduate students - Azzahrah, Anuar; Edris, Aden; Heng, Chin Siong; Mohamad Azhari, Abu Bakar (Centre for Applied Learning and Multimedia (CALM) , UNIMAS 2024, 2024)
Including team-based assessments is considered essential for preparing students to face challenges in their professional careers. This study aims to assess the levels of emotional and cultural intelligence among undergraduate students, as well as their general attitudes toward courses involving team-based assessments. A total of 223 participants were involved in the research. The study also explores how emotional and cultural intelligence relate to attitudes towards team-based assessments. These findings highlight the role of emotional and social competence in enhancing student engagement in team-based learning and assessments.